2015
DOI: 10.4103/2278-9626.163341
|View full text |Cite
|
Sign up to set email alerts
|

Retreatment of endodontically failed tooth with wide-open apex using platelet rich fibrin membrane as matrix and an apical plug of Biodentine™

Abstract: The primary reason for an endodontic failure is the persistence or regrowth of bacteria within the root canal system, and such cases require retreatment. The tooth root development and closure of its apex occurs till 3 years after the eruption. Traumatic injuries during this development period result in endodontic complications. While dealing with a tooth, with an open apex the prime objective was eliminating bacteria from the root canal system with minimum irritation to the periapical tissues and induction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Pawar et al [ 17 ] reported healing of periapical lesion in a failed attempt of revascularization, when MTA and PRF were used together.…”
Section: Discussionmentioning
confidence: 99%
“…Pawar et al [ 17 ] reported healing of periapical lesion in a failed attempt of revascularization, when MTA and PRF were used together.…”
Section: Discussionmentioning
confidence: 99%
“…Thermo-plasticized gutta percha technique is not recommended for the tooth with periapical lesion and open apex, without apical barrier matrix because of wide apical foramen and uncontrolled length of working distance [ 1 , 10 , 16 , 17 , 28 ]. Once the apical plug of MTA has been established, any obturation techniques could have been performed to fill the remaining space of the root canal.…”
Section: Discussionmentioning
confidence: 99%
“…The literature shows that no instrument or technique can completely remove root canal filling materials from the root canal system during non-surgical root canal retreatment [1], [3], [13], [14], [15], [16], [17] which can ultimately result in treatment failures because of the inability to eliminate microorganism from the root canal system [4]. Therefore, new instruments and supplementary protocols for remaining filling material removal have been proposed [5], [18], [19], [20].…”
Section: Discussionmentioning
confidence: 99%
“…The primary reason for an endodontic failure is the persistence or regrowth of bacteria within the root canal system which requires retreatment [1], the success of retreatment depends on the efficient removal of the entire root filling material from the root canal system [2].…”
Section: Introductionmentioning
confidence: 99%